Ceramic fragmentation after total hip arthroplasty: two case reports and literature review - Wu, Tingyu; Guo, Sijia; Jiang, Yaping; Shi, Weipeng; Wang, Yingzhen; Li, Tao (Frontiers in Surgery, 2024)
Background: Ceramic fragmentation is a rare but serious complication after total hip arthroplasty (THA). We reviewed the PubMed literature from 1990 to 2023 and found only 31 case reports of ceramic fragmentation after THA. Our case reports help to expand understanding of this rare complication. We shared our surgical experience and identified an ideal material for revision surgery, which can serve as a useful reference for other orthopedic surgeons to perform ceramic fragmentation revision surgery in the future. We also analyzed the possible causes, diagnosis, and treatment opinions of ceramic fragmentation.Case presentation: This study presents two cases of ceramic fragmentation after THA. One patient had ceramic head fragmentation 10 years after the primary THA, and one patient had ceramic liner fragmentation 5 years after the primary THA. Both patients presented with pain, and one patient also reported a clicking sound in the hip. The two patients described here had BMIs of 23.7 and 23.1, respectively. Both patients' ceramic fragmentation were due to aseptic loosening, not periprosthetic joint infections, as confirmed by negative microbiological cultures. Radiographic examinations of both patients revealed radio-opaque wear debris around the hip joint prostheses and we describe the surgical protocols and intraoperative findings in both cases in detail.Our cases and the literature suggest that ceramic fragmentation can occur at any time after THA. The most immediate symptoms are pain and noise, but some patients may be asymptomatic. Ceramic on polyethylene bearings is recommended for revision surgery whenever possible; metal bearings should be avoided.